A new record of the spiny lobster, Panulirus femoristriga (von Martens, 1872) from the coastal waters of Malaysia, with revision of global distribution - Ng, Wei Ling; Chen, Cheng Ann; Saleem Mustafa; Leaw, Chui Pin; Teng, Sing Tung; Siti Nor Fatihah Binti Zakaria; Audrey Daning Tuzan; Chan, Tin-Yam (Pensoft Publishers, 2022)
Background Spiny lobsters of the family Palinuridae Latreille, 1802 are known to be industrial crustaceans in the global fishing market amongst other crustacean marine species. Panulirus femoristriga has been reported in the Maldives, Japan, Taiwan, Vietnam, the Philippines, Indonesia (Ambon, Irian Jaya, Celebes Island, Seram Island), the Polynesian Islands, Solomon Islands, New Hebrides, Wallis and Futuna and off the coast of northern Australia, but there is uncertainty about their distributions due to the morphological similarity with Panulirus femoristriga, Panulirus longipes bispinosus and Panulirus brunneiflagellum. However, the identification on P. femoristiga can only be confirmed if the morphological descriptions are mentioned in literature.